Application of The Concept “Ngugemi Ajaran Leluhur” To Prevent Mon-ey Politics in Sedulur Sikep Community in Pati, Central Java - Sri Wahyu Ananingsih; Sukirno Sukirno; Agung Basuki Prasetyo; Faishal Hafizha A (Green Publisher Indonesia, 2024)
The practice of money politics is one type of electoral and regional election crime. In practice, not all money politics cases can proceed to the Courts. For example,based on data from the Bawaslu of Central Java Province, the number of alleged money politics in the 2019 election was 66 cases. Of the 66 cases that can be processed to court, only 5 cases. This can be stated that so far law enforcement against cases of money political practices in elections has not been optimal. Therefore, repressive and preventive efforts are needed. One of the preventive efforts as carried out by the Sedulur Sikep community living in Baturejo Village, Sukolilo District, Pati Regency. This community applies the concept of